(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The use of electronic communication as a learning tool helps to partially solve one of the main tasks of learning - the creation of a natural language environment, since it provides additional opportunities for communication in the target language. The natural communication environment based on such means of electronic communication as e-mail, chat communication, forums, guest books, online diaries, can be used by Russian as a foreign language teachers to maintain and improve the level of knowledge, assess students’ speech behavior in different communicative situations.